(untitled) (NAU Journal of Technology and Vocational Education, 2025)
The purpose of this study was to investigate the challenges and prospect of the implementation of universal basic education in some selected junior secondary school in southern senatorial zone, Nasarawa state. Specifically, the study sought: to determine the level of universal basic education. The study was carried out in southern senatorial zone, namely: Awe, Doma, Keana, Lafia and Obi local government Areas in Nasarawa State. The population for the study comprised 735 teachers and 68 principals using random sample technique. The study sampled 246 teachers and 15 principals. The data was collected by use of questionnaire. Percentage, mean, and standard deviation were used to answer the two research questions. Some of the findings of the study showed that there are positive impacts of Universal Basic Education programme in southern senatorial zone of Nasarawa State, an increase in equity in participation by students of different backgrounds. Some challenges facing the full implementation of universal basic education in the zone include poor education statistics, inadequate publicity, inadequate funding, and inadequate infrastructure. The Study recommends among others that fund available should be effectively utilized at the targeted areas they are meant for; more teachers should be employed for the UBE programme.